Multimedia Big Data Processing Techniques: a Survey - ., Chaithra; Fernandes, Roshan (International Journal of Engineering and Technology, 2018)
Massive amount of multimedia information are used in day to day life, especially in social media such as Facebook, Whatsapp, Instagram etc. Along with this, most of the real time applications, produce large scale video data which has to be continuously monitored, analysed and processed, so that easier interpretation of required patterns can be done, and real time applications such as detecting traffic flow, predicting weather can be eased out. In this paper, the various existing work done on multimedia big data processing using Hadoop have been discussed. A review on Hadoop-MapReduce system along with HDFS and how multimedia processing has been done in a parallel and distributed manner using it, have also been examined and discussed. In addition to that, the availability and benefits of Real time big data processing tools, methods, and framework such as Apache Spark is been highlighted, and need for the discovery of much more better real time multimedia big data processing frameworkÂ have been talked about.Â Â